Realitas Elit Politik Lokal dan Persepsi Masyarakat dalam Proses Pemekaran Daerah - Hilal Ramdhani (Universitas Medan Area, 2019)
This article aims to understand and identify that Cirebon Province has not yet been formed, even though there has already been a discourse on the formation of Cirebon Province, marked by the establishment of the Cirebon Province Expansion Committee (P4C) since 2009. In order to approach this problem, the theory of political elite from Geatano Mosca is used, the theory explains that elite action is a form of the will of the community, so that it is understood that there is a link between community views and actions taken by political elites. Data is collected through the observation of the actions of political elites in the regions of Cirebon Regency, Cirebon City, Indramayu Regency, Kuningan Regency and Majalengka Regency, and conducting interviews with the community in the Cirebon Regency, Cirebon City, Indramayu Regency, Kuningan Regency and Majalengka Regency. Data analysis was carried out qualitatively using data reduction, data presentation and drawing conclusions. This study concludes that until 2019 the local political elite of Kab. Majalengka and Kab, Kuningan still did not agree to join the Cirebon Province, while the political elite of Kab. Cirebon, Cirebon City and Regency, Indramayu agreed to form the province of Cirebon, the decision of the political elite turned out to be in accordance with the perception of the people who refused or supported joining to form the Cirebon Province.